"Memorias dun neno labrego": the Making of a Longseller - Galanes Santos, Iolanda (Madrygal. Revista de Estudios Gallegos, 2017)
The work Memorias dun neno labrego (Memoirs of a Peasant Boy) by Xosé Neira Vilas, considered as the best seller of the Galician literature has been subject to several classifications from its first publication to the present.The general objective of this paper is to delve deep into emigration literature in order to ascertain its significance for the Galician literary system, through a study of the author’s journey and of the work in context, as well as its reception. A second objective is to look at the processes of production and edition of a Galician literary work that has become successful internationally and over time. The study methodology consists of the systematic analysis of the peritexts of the published work, of the inherent postal correspondence of the author and of the literary criticism in order to ascertain, through the reception of the work the significance gained over the past fifty-five years. This journey offers information which leads us to conclude that Memoria is a work about emigration, a longseller. Besides compiling critical information, this study throws new light on two singular publication projects (Follas Novas and Rúa Nova) which included it or intended to include it in their catalogue.
Keywords: Neira Vilas; Longseller; Representative Literary Work; Emigration Literature; Galician Literature; Cultural Sociology.